2020
DOI: 10.1016/j.ygyno.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer symptoms, routes to diagnosis and survival – Population cohort study in the ‘no screen’ arm of the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS)

Abstract: Objective There are widespread efforts to increase symptom awareness of ‘pelvic/abdominal pain, increased abdominal size/bloating, difficulty eating/feeling full and urinary frequency/urgency’ in an attempt to diagnose ovarian cancer earlier. Long-term survival of women with these symptoms adjusted for known prognostic factors is yet to be determined. This study explored the association of symptoms, routes and interval to diagnosis and long-term survival in a population-based cohort of postmenopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 26 publications
6
45
2
Order By: Relevance
“…Our finding that the majority of women with an eventual diagnosis of ovarian cancer had 1 of the classic symptoms included on a validated symptom screening index speaks to the importance of having a high index of suspicion for ovarian cancer, even when these symptoms may not be the primary reason for a visit. Even though the absolute differences in TTD in our study were often small, even small differences in TTD may affect cancer survival, 14,19,22 and efforts should be taken to minimize any delays in diagnosis.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Our finding that the majority of women with an eventual diagnosis of ovarian cancer had 1 of the classic symptoms included on a validated symptom screening index speaks to the importance of having a high index of suspicion for ovarian cancer, even when these symptoms may not be the primary reason for a visit. Even though the absolute differences in TTD in our study were often small, even small differences in TTD may affect cancer survival, 14,19,22 and efforts should be taken to minimize any delays in diagnosis.…”
Section: Resultsmentioning
confidence: 72%
“…Studies suggest that the mean time from the onset of ovarian cancer symptoms to diagnosis ranges from 1.4 to 10.0 months and depends on the type and number of symptoms, route to diagnosis, and diagnostic workup. 2,[14][15][16][17] However, these reports are largely small observational studies or have been conducted internationally and thus represent dissimilar health care systems in comparison with the United States. Although controversial, [18][19][20][21][22] recent studies have suggested that a faster TTD may positively affect cancer survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some symptoms of ovarian cancer may be confused with those of benign and more prevalent diseases, which can prevent timely visits for medical treatments (23). Early visits to medical centers after observing any symptoms of ovarian cancer can be associated with better therapeutic outcomes (24). In this study, 7.7% of participants stated that they will wait several months before visiting a medical center if they suspect the warning signs of ovarian cancer, and 10.8% of them said that they would never seek medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are of special importance because the warning signs of ovarian cancer can be confusing for women. Because symptoms such as abdominal pain, anorexia, and a constant sense of fullness have been reported to be associated with the increased mortality risk (24), it is critical to raise women's awareness of the warning signs of ovarian cancer. The lowest level of awareness about risk factors was related to IVF treatment history (21.3%) and the application of talcum powder to the genital area (25.4%).…”
Section: Discussionmentioning
confidence: 99%